2018
DOI: 10.1002/hed.25538
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of computed tomography combined with ultrasonography in detecting cervical recurrence in patients with thyroid cancer

Abstract: Background To determine the diagnostic role of CT added to ultrasound for the diagnosis of recurrent differentiated thyroid cancer (DTC) and to evaluate potential benefits for patients. Methods A total of 193 patients with recurrent DTC were retrospectively included. The diagnostic performances of ultrasound and combination of ultrasound and CT (ultrasound/CT) in detecting recurrence were compared. Benefits of CT were assessed based on the presence of any recurrence detected only with additional CT. Results In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…CT may also be used in cases where US may not adequately visualize disease recurrence, especially in those patients with high serum Tg or Tg antibodies and negative US [ 21 84 234 ]. A recent study demonstrated the added value of CT to US for the detection of thyroid cancer recurrence [ 262 ]. Before revision surgery or image-guided intervention, target lesions should be accurately identified using both US and CT [ 21 ].…”
Section: Role Of Ct In Thyroid Cancer Diagnosismentioning
confidence: 99%
“…CT may also be used in cases where US may not adequately visualize disease recurrence, especially in those patients with high serum Tg or Tg antibodies and negative US [ 21 84 234 ]. A recent study demonstrated the added value of CT to US for the detection of thyroid cancer recurrence [ 262 ]. Before revision surgery or image-guided intervention, target lesions should be accurately identified using both US and CT [ 21 ].…”
Section: Role Of Ct In Thyroid Cancer Diagnosismentioning
confidence: 99%
“…These modest detection rates may warrant the addition of computed tomography (CT) or a USG-guided FNAC in revision cases to avoid unnecessary reoperations. However, the literature for the same is not adequate, and a study by Hong et al recommends combining CT and USG to increase sensitivity in detecting cervical recurrence in thyroid cancers [18]. A meta-analysis by Zhao et al reported a sensitivity of 33%, 70%, specificity of 93%, 84% by USG, in detecting central and lateral neck nodes respectively among previously untreated patients with papillary thyroid cancer [19].…”
Section: Follow-up and Disease Outcomesmentioning
confidence: 99%